Underlying Mechanism of Jiuwei Shengmai Powder in Improving Myocardial Hypoxia at High Altitude Based on Network Pharmacology and Molecular Docking - Cong Wu; Yanjuan Zhu; Changpeng Xie; Haobo Liu; Yuanming Pan; Chang'e Liu (iLabmed)
ABSTRACT Background High altitude shock is attributed to myocardial ischemia and hypoxia. Jiuwei Shengmai powder has positive impacts on human physiology. However, it is unknown if it can mitigate myocardial ischemia and hypoxia. This study aimed to postulate the molecular mechanism that relieves myocardial hypoxia injury in officers and soldiers at high altitude after ingesting Jiuwei Shengmai powder by using network pharmacology and molecular docking. Methods The effective components and potential targets of Jiuwei Shengmai powder were detected by databases such as the traditional Chinese medicine systems pharmacology (TCMSP), PubChem, and UniProt. Target genes related to myocardial hypoxia injury were identified using Gene Cards, Online Mendelian Inheritance in Man, DrugBank, DisGeNET, the Comparative Toxicogenomics Database, and other databases. CytoScape was used to construct a “drug‐active ingredient‐target gene” network. Protein‐protein interactions (PPIs) were predicted using the STRING database. Core gene target data were analyzed using Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment utilizing R packages, while Autodock Vina was used to verify the molecular docking simulation. Results One hundred and sixteen active ingredients were identified in Jiuwei Shengmai powder and were shown to target 197 genes. Of these, 3073 core target genes were related to myocardial hypoxia injury, and 130 core genes were obtained after Veen intersection. There were 129 PPI nodes and 1769 edges. The docking binding energy was ≤ −5.0 kcal·mol−1, indicating strong binding between the active compounds and targets. Quercetin and kaempferol are the main components in Jiuwei Shengmai powder that relieve myocardial hypoxia injury. Their core targets are interleukin‐6 and activated cysteine proteinase‐3 antibody, which are mainly related to PI3K‐Akt‐, mitogen‐activated protein kinase (MAPK), tumor necrosis factor (TNF), and interleukin 17 (IL‐17) signaling pathways. Conclusions This study provides a strong theoretical basis to understand the interaction of the components in Jiuwei Shengmai powder with human genes and proteins that should help to plan biochemical studies to better understand myocardial hypoxia injury mitigation.